Spontaneous pneumocephalus presenting with apnea attacks in a newborn with open myelomeningocele - Erol, FS; Kaplan, M (Karger, 2004)
We report a case who had an open myelomeningocele and developed respiratory arrest associated with spontaneous pneumocephalus. Spontaneous respiration resumed after closing of the defect and ventriculoperitoneal shunting. We conclude that repairment of the defect in the early period is very useful both to minimize the infection risk and to prevent the complication of pneumocephalus in these cases. Copyright (C) 2004 S. Karger AG, Basel.
Keywords: apnea; myelomeningocele; spontaneus pneumocephalus